2007
DOI: 10.3892/ijmm.19.6.933
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors for lone atrial fibrillation

Abstract: Abstract. Atrial fibrillation (AF) may result from an electric conduction disturbance, increased hemodynamic stress, ischemia, inflammation, or remodeling in atria. Although genetic epidemiological studies have identified several genetic variants as risk factors for AF, the genetic determinants of this condition remain largely unknown. The purpose of the present study was to identify gene polymorphisms that confer susceptibility to lone AF. The study population comprised 1069 unrelated Japanese individuals, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
0
28
1
7
Order By: Relevance
“…In the human heart, PITX2c is the major isoform expressed 19 and is involved in the control of asymmetric cardiac morphogenesis. 15,20 Chung et al 21 have shown the association of a genetic variant on chromosome 4q25 with levels of PITX2c transcripts in left atrial tissue samples and knockout mouse models have indicated a critical role of the PITX2c in the development of the left atrium. 22 Of note, PITX2c was in a recent study demonstrated to be a requisite for the development of a sleeve of cardiomyocytes extending from the left atrium to the initial portion of the pulmonary veins, which is believed to be the anatomical substrate for AF and the fundament for pulmonary vein isolation when an ablation strategy is chosen in an AF patient.…”
Section: The 4q25 Locusmentioning
confidence: 99%
“…In the human heart, PITX2c is the major isoform expressed 19 and is involved in the control of asymmetric cardiac morphogenesis. 15,20 Chung et al 21 have shown the association of a genetic variant on chromosome 4q25 with levels of PITX2c transcripts in left atrial tissue samples and knockout mouse models have indicated a critical role of the PITX2c in the development of the left atrium. 22 Of note, PITX2c was in a recent study demonstrated to be a requisite for the development of a sleeve of cardiomyocytes extending from the left atrium to the initial portion of the pulmonary veins, which is believed to be the anatomical substrate for AF and the fundament for pulmonary vein isolation when an ablation strategy is chosen in an AF patient.…”
Section: The 4q25 Locusmentioning
confidence: 99%
“…40,[46][47][48][49][50][51][52][53][54][55][56][57][58] Candidate gene studies focus on specific genes that are selected based on a priori knowledge of their function, and compare the frequency of the variants between cohorts of individuals with and without disease. 59 To date, a number of candidate-gene association studies have identified common variants that are more prevalent in AF populations compared with control populations.…”
Section: Common Genetic Variants and Atrial Fibrillation In The Genermentioning
confidence: 99%
“…59 To date, a number of candidate-gene association studies have identified common variants that are more prevalent in AF populations compared with control populations. 40,[46][47][48][49][50][51][52][53][54][55][56][57][58] Often, the candidate genes have been selected based on results of studies in familial AF. As summarised in Table 2, a The recent advent of GWAS has led to significant progress in our understanding of the genetic basis of AF.…”
Section: Common Genetic Variants and Atrial Fibrillation In The Genermentioning
confidence: 99%
“…Причиной возникновения аритмии может быть воспаление, ишемия и ремоделирование предсер-дий [3]. Кроме того, некоторые генетические полимор-физмы и внешние факторы могут играть роль в увели-чении восприимчивости организма к развитию ФП [4]. Данные литературы свидетельствуют о значимости кли-нических и генетических параметров в инициировании послеоперационной ФП (ПОФП) [3,5].…”
unclassified
“…IL-10 участвует в прогрессировании различных заболеваний, в частности, сердечно-сосу-дистой патологии. Данные литературы свидетель-ствуют о взаимосвязи между полиморфизмами IL10 C592A и риском возникновения ФП [4].…”
unclassified